The Effect of Talent Management on Employee Retention in Indonesian Banking Industry - Prastiyo Diatmono (Maneggio, 2026)
The Indonesian banking industry faces significant challenges in retaining qualified employees due to intense competition and high workforce mobility. This condition positions employee retention as a strategic issue closely related to organizational stability and performance sustainability. This study aims to examine the influence of talent management on employee retention in the Indonesian banking industry. A quantitative explanatory design was employed involving 215 permanent employees from national commercial banks (conventional and Islamic) operating in urban areas of Indonesia. Data were analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software. The results reveal that talent management has a positive and statistically significant effect on employee retention (β = 0.62; p < 0.001). The R² value of 0.38 indicates that talent management explains 38% of the variance in employee retention. The predictive relevance test (Q² = 0.24) confirms that the model has adequate predictive capability. Furthermore, the effect size (f² = 0.38) demonstrates a large substantive impact of talent management on employee retention. These findings confirm that talent management functions as a strategic mechanism rather than a purely administrative practice in the banking sector. The study contributes theoretically to the human resource management literature and provides practical insights for banking institutions in designing sustainable talent management strategies to enhance employee retention.